CaO-based CO2 sorbents: A review on screening, enhancement, cyclic stability, regeneration and kinetics modelling. (January 2018) - Salaudeen, Shakirudeen A.; Acharya, Bishnu; Dutta, Animesh
Highlights: Extensive review has been carried out on metal-based CO2 sorbents with special attention on calcium oxide. Discussion on the challenges in sorbent performance is included in the article. Available techniques for the enhancement, stability and regeneration of sorbents are discussed in the work. Kinetic models of the carbonation conversion from the classical to the recent advances are reported in this review. Recommendations for future studies are suggested. Abstract: This article reviews current developments in metal-based sorbents for carbon capture with emphasis on calcium oxide. A broad overview of carbon dioxide capture with metals in various forms including oxides, hydroxides, carbonates and zirconates is presented. Based on the findings from comparative assessments of these sorbents, CaO appears to be the best solid sorbent for CO2 capture at high temperatures, and its numerous advantages are discussed in this work. For this reason, a detailed review has been conducted for calcium oxide, which works as a sorbent at temperatures up to 700 °C through carbonation, and desorbs CO2 above 700 °C by calcination of CaCO3 at atmospheric pressure. A review of studies on kinetics modelling of CO2 capture with CaO-based sorbents is also included in this work. Decay in activity caused by sintering and attrition is identified as the greatest challenge with CaO-based sorbents. This work also focuses on the available techniques for enhancing performance and cyclic stability. Reactivation of the sorbents by hydration and reduction in decay rate by doping with inert supports and synthetic sorbents are reviewed. Additionally, the use of biomass resources (waste animal shells) as competitive sources of CaCO3 is discussed in this work. The review concludes with recommendations for future studies in carbon capture and sequestration.